Design, Environmental Validation, and Candidate Crop Screening in a Modular Micro-Lunar Greenhouse System under CELSS-Like Conditions - Tao Wei; Olha Bakumenko; Yunfan Zhang (Three E Science Institute, 2026)
Controlled Ecological Life Support Systems (CELSS) require reliable in situ crop production for long-duration lunar and planetary habitation. However, existing research infrastructure remains divided between large, expensive facilities and conventional growth chambers that lack the environmental realism needed for standardized crop screening. This study aimed to design, engineer, and experimentally validate a Micro-Lunar Greenhouse System (MLGS) as a mid-scale modular platform for evaluating functionally diverse candidate crops under CELSS-like conditions. The 1.52 m3 MLGS integrated automated control of atmospheric composition, temperature, relative humidity, airflow, hydroponics, and programmable LED lighting across three independent cultivation zones. Mesembryanthemum crystallinum, Anredera cordifolia, and Anoectochilus roxburghii were cultivated for 180 days under species-optimized MLGS conditions and compared with standard laboratory chamber conditions using three biological replicates per treatment. Platform performance and crop responses were assessed through environmental stability, growth, photosynthetic traits, nutritional and bioactive composition, resource-use efficiency, waste-processing capacity, and microbial safety. The MLGS maintained environmental setpoints within ±0.8°C, ±1.5% relative humidity, and 25-35 ppm CO2 of target values for more than 97% of operating time, with low spatial heterogeneity among cultivation zones. Relative to the control, the optimized MLGS treatment increased biomass by 38-62%, enhanced key nutritional or bioactive compounds by 24-46%, and improved water-use efficiency by 25-55%. Nitrogen and phosphorus removal from simulated waste streams reached 58-79% and 47-70%, respectively, and no foodborne pathogens were detected. These results validate the MLGS as a reproducible bridge platform between large CELSS facilities and conventional growth chambers, supporting standardized crop screening for future space agriculture applications.